PENGARUH PROFITABILITAS DAN NILAI PASAR TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Fathonah, Nurul Ulfah SIti (2013)
A shareholder purpose in investment to gain the return which is earned by the company.The phenomena on this research is the decline of stock price food and beverage subsector during 2007-2012. So that, the stock return was earned by food and beverage subsector during 2007-2012 inclining decline. The research purposes to know profitability description is measured by Return On Equity (ROE), market value by Price Earning Ratio (PER) and stock return on food and beverage subsector companies in Indonesia Stock Exchange. Beside that, to determine the influence of Return on Equity (ROE) and Price Earning Ratio (PER) to stock return The research method used descriptive method and verification method. And analysis technique which used is double linier regression analysis, product moment correlation and determination coefficient analysis. Meanwhile, the hypotheses test used F-test and T-test. Data which used is secondary data ROE, PER and stock return on food and beverage subsector companies in Indonesia Stock Exchange during 2007 - 2012. ROE and PER are significant to the stock return. According to simultaneous test (F-test) showed that ROE and PER jointly influenced significantly to the stock return. The value of R2 is 0,182 showed that the influences of ROE and PER to the stock return as much 18,2% while other remaining as much 81,8% is influenced by other variables. Keywords: Profitability, Market Value, Return OnEquity, Price Earning Ratio, Stock Return.